Effectiveness of Treatment for Distal Tibial Nonunions With Associated Complex Deformities Using a Hexapod External Fixator. Issue 2 (February 2017) - Arvesen, John E.; Tracy Watson, J.; Israel, Heidi
Abstract : Objective: To determine the efficacy of a hexapod external fixator (TSF) and its ability to perform 6-axis correction in restoring deformities associated with distal tibial nonunions. Design: Consecutive retrospective case review. Setting: St. Louis University Hospital. Level 1 Trauma Center. Patients/Participants: Thirty-seven patients with distal tibial nonunion with greater than 5 degrees of deformity in any plane. Patients were excluded who were less than 18 years of age, had tibial deformities less than 5 degrees, had proximal or middle tibial deformities, or had less than 1 year of follow-up. Intervention: Patients with distal tibial nonunions with combined deformities were treated by the senior author with a hexapod device. Preoperative mechanical axis deviation and union status were assessed. Postoperative parameters evaluated included anatomic and mechanical axis determination and adequacy of union. Metrics include long alignment films with routine clinical follow-up. Main Outcome Measurements: Assessment of deformity correction in 6 axes, restoration to union, and mechanical axis correction. Results: Average combined preoperative deformity was greater than 17.7 degrees. Average mechanical axis was restored within 5 degrees of the desired goal in all categories except in patients with severe preoperative valgus deformities. The complex nonunion group had a 94% union rate. Average time in the hexapod was 106.7 days. Average follow-up time was 2 years. Conclusions: Hexapod external fixators can be used as an accurate modality to heal complex distal tibia nonunions with multifocal deformities and significant mechanical axis deviation. These difficult reconstructions are accomplished with minimum complications using these devices. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.